The Development of Microsoft Powerpoint-Assisted Worksheet to Increase Students’ Mathematical Problem Solving Ability - Rizky Yuniar; Heris Hendriana; R Kurniawan; Anik Yuliani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
SMP Al-amin is a private school located in the district of Kandanghaur - Indramayu. The learning resources provided by the Government only provide books for teachers and do not provide worksheet to students. Therefore the researcher wants to make PowerPoint-assisted worksheets to increase enthusiasm, student interest in learning, and student motivation while studying. The purpose of this research is to produce student worksheets assisted by Microsoft PowerPoint. The research method used is research and development (R&D) and the ADDIE learning design. The stages of the ADDIE development model are as follows: analysis, design, development, implementation, and evaluation. The subjects of this study were class VIII students of SMP Al-Amin Kandanghaur. the instruments used were feasibility analysis, student response questionnaires, and teacher response questionnaires. Based on the research findings, the PowerPoint-assisted worksheet was declared "feasible" with a feasibility value of 80%. In addition, the student and teacher response questionnaire rates were 79%, indicating that these PowerPoint-assisted worksheets are "handy". Thus it can be concluded that the use of PowerPoint-assisted WORKSHEET in the two-variable linear equation system (SPLDV) subject can be said to be a safe, practical, and effective learning mediumkeywords.